Working with layers: The governance and regulation of healthcare quality in an institutionally layered system. (January 2017) - van de Bovenkamp, Hester M; Stoopendaal, Annemiek; Bal, Roland
Institutional arrangements used to steer public policies have increasingly become layered. Inspired by the literature on institutional layering and institutional work, this paper aims to make a contribution to our understanding of institutional layering. We do so by studying an interesting case of layering: the Dutch hospital sector. We focus on the actors responsible for the internal governance (Board of Directors and Supervisory Boards) and the external regulation (the Healthcare Inspectorate) of hospitals. In the paper, we explore the institutional work of these actors, more specifically how institutional work results from and is influenced by institutional layering and how this in turn influences the institutional makeup of both healthcare organizations and their institutional context. Our approach allowed us to see that layering changes the activities of actors in the public sector, can be used to strengthen one's position but also presents actors with new struggles, which they in turn can try to overcome by relating and using the institutionally layered context. Layering and institutional work are therefore in continuous interaction. Combining institutional layering with a focus on the lived experiences of actors and their institutional work makes it possible to move into the layered arrangement and better understand its consequences.